(untitled) (Research, Society and Development, 2022)
This work aimed to analyze the economic viability of wind energy generation in the urban area of Cascavel - PR, with the purpose of meeting the demand of a single-family residence. The experiment was conducted through the collection and analysis of performance data of a small Greatwatt wind turbine, model S-600, installed in the Alternative Systems Analysis Center (CASA), of the Cascavel campus of the Universidade Estadual do Oeste do Paraná (Unioeste). For this purpose, the information on the production of electricity from the turbine and the available wind energy was obtained in a field test by measuring wind speed values, voltage and current supplied by the wind turbine to a set of electrical resistors that simulate the household load and were collected by a data acquisition system consisting of a Campbell CR1000 Datalogger. The data collected at the end of the experiment showed a production of 1.23 kWh in the 25 days of collection with a total availability of 6.6 kWh, resulting in a yield of 18.7%. With these data, an analysis of the economic viability of the implementation of the system in a residence in the region was carried out, concluding that the system is still economically unviable, as it does not cover its implementation costs at the end of its useful life.